2016
DOI: 10.1186/s40645-016-0093-6
|View full text |Cite
|
Sign up to set email alerts
|

Imaging in 3D under pressure: a decade of high-pressure X-ray microtomography development at GSECARS

Abstract: The high-pressure X-ray microtomography (HPXMT) apparatus has been operating at the GeoSoilEnviroCARS (GSECARS) bending magnet beamline at the Advanced Photon Source since 2005. By combining the powerful synchrotron X-ray source and fast switching between white (for X-ray diffraction) and monochromatic (for absorption imaging) modes, this technique provides the high-pressure community with a unique opportunity to image the three-dimensional volume, texture, and microstructure of materials under high pressure a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 31 publications
(48 reference statements)
0
12
0
Order By: Relevance
“…At present, all of the current synchrotron light sources capable of hard X-ray imaging are using SXR-mCT for earthsciences-related research. The most prominent example is the GSECARS group at the Advanced Photon Source, which has also pioneered the use of environmental cells for in situ imaging (Rivers et al, 1999;Rivers & Wang, 2006;Yu et al, 2016), with an emphasis on extreme temperature (T) and pressure (P) measurements using the Paris-Edinburgh type of cell (see also : Bromiley et al, 2009), similar in concept to those used for neutron and X-ray diffraction experiments (Besson et al, 1992;Le Godec et al, 2005). Other SXR-mCT synchrotron beamlines currently work on a regular basis with geoscientist users and developing their own in situ devices (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…At present, all of the current synchrotron light sources capable of hard X-ray imaging are using SXR-mCT for earthsciences-related research. The most prominent example is the GSECARS group at the Advanced Photon Source, which has also pioneered the use of environmental cells for in situ imaging (Rivers et al, 1999;Rivers & Wang, 2006;Yu et al, 2016), with an emphasis on extreme temperature (T) and pressure (P) measurements using the Paris-Edinburgh type of cell (see also : Bromiley et al, 2009), similar in concept to those used for neutron and X-ray diffraction experiments (Besson et al, 1992;Le Godec et al, 2005). Other SXR-mCT synchrotron beamlines currently work on a regular basis with geoscientist users and developing their own in situ devices (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Efforts have also been made to perform nano-imaging in a diamond-anvil cell using X-ray transparent beryllium gaskets, and iterative methods to overcome the 'limited projections problem' (Liu et al, 2008;Wang et al, 2012;Lin et al, 2013). In practice, only GSECARS at the Advanced Photon Source at Argonne National Laboratory has the capability of performing absorption-based tomography in large-volume samples under high pressure ($ 10 GPa), high temperature ($ 1500 K) and deformation, using a modified Drickamer cell allowing the full rotation of the sample chamber under load (Wang et al, 2005;Yu et al, 2016). This device has been successfully used to study the volumetric properties of non-crystalline materials (Lesher et al, 2009), and the deformation behavior of multi-phase composites under shearing (Wang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Two review and seven research articles from that session are included in this SPEPS. These articles cover Earth's formation/evolution (de Vries et al 2016;Kondo et al 2016), magma and fluid in the interior of the Earth (Mysen 2015;Ohira et al 2016;Poli 2016;Reynard 2016), Earth's deep mantle (McCammon et al 2016;Zhang et al 2016), and methods using synchrotron radiation (Yu et al 2016).Giant impact events during planetary accretion caused large degrees of melting of the early Earth. De Vries et al (2016) simulated the volumes of melt, pressure, and temperature conditions of metal-silicate equilibration after each impact, and demonstrated that the pressure evolution during metal-silicate equilibration during accretion depends strongly on the lifetime of impactgenerated magma oceans compared to the time interval between large impacts.…”
mentioning
confidence: 99%
“…Two review and seven research articles from that session are included in this SPEPS. These articles cover Earth's formation/evolution (de Vries et al 2016;Kondo et al 2016), magma and fluid in the interior of the Earth (Mysen 2015;Ohira et al 2016;Poli 2016;Reynard 2016), Earth's deep mantle (McCammon et al 2016;Zhang et al 2016), and methods using synchrotron radiation (Yu et al 2016).…”
mentioning
confidence: 99%
See 1 more Smart Citation